Differentially expressed tRNA-derived fragments and their roles in primary cardiomyocytes stimulated by high glucose - Zhao, Yongting; Wang, Ruxin; Qin, Qi; Yu, Jiaojiao; Che, Hui; Wang, Lihong (Frontiers in Endocrinology, 2023)
Diabetic cardiomyopathy (DCM) is a serious complication of diabetes mellitus that can cause malignant arrhythmia and sudden death and is associated with cardiomyocyte dysfunction induced by hyperglycemia. Emerging evidence has revealed that transfer RNA-derived fragments (tRFs), a novel class of noncoding RNAs, play a crucial role in a variety of pathophysiologic processes, including cell death, cell growth and proliferation. However, it remains unknown whether and how tRFs are involved in cardiomyocyte dysfunction during the progression of DCM. In this study, we found that cardiomyocyte abnormalities were induced by high glucose (HG) treatment, as demonstrated by a decrease in cell viability and autophagy activation as well as an increase in cell death and proinflammatory cytokine release. Moreover, HG treatment resulted in differential expression of tRFs in cardiomyocytes, of which 4 upregulated and 1 downregulated tRFs were observed compared with the control group. The differential expression of 4 upregulated tRFs was primarily involved in cardiac dysfunction-related processes, such as autophagy, AGE-RAGE signaling pathway in diabetic complications, MAPK signaling pathway, insulin signaling pathway, FoxO signaling pathway, insulin resistance and peroxisome pathways based on Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Furthermore, we found that tRF-5014a, the most significantly upregulated tRF among all tested tRFs, negatively regulated the expression of the autophagy-related protein ATG5. Importantly, inhibition of tRF-5014a not only abolished autophagy inactivation but also attenuated the decrease in cell viability and increase in cell death as well as proinflammatory cytokine release under HG conditions. These findings suggest that tRFs may contribute to HG-induced cardiomyocyte injury during DCM progression.